2021
DOI: 10.3389/fpsyt.2021.691930
|View full text |Cite
|
Sign up to set email alerts
|

Stop What You're Doing!—An fMRI Study on Comparisons of Neural Subprocesses of Response Inhibition in ADHD and Alcohol Use Disorder

Abstract: Rationale: Both attention deficit-/hyperactivity disorder (ADHD) and alcohol use disorder (AUD) are accompanied by deficits in response inhibition. Furthermore, the prevalence of comorbidity of ADHD and AUD is high. However, there is a lack of research on whether the same neuronal subprocesses of inhibition (i.e., interference inhibition, action withholding and action cancellation) exhibit deficits in both psychiatric disorders.Methods: We examined these three neural subprocesses of response inhibition in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…We did not suspect any overlap between the studies because the studies with the same authors differed in terms of the sample studied, the collection parameters, the study design, and the demographic characteristics. The study by Gerhardt et al ( 2021 ) investigated both GNGT and SST paradigm in the same sample. We have treated these data as a single experiment because splitting the experiments into two different ones would suggest statistical independence, which we argue is not given by using the same sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not suspect any overlap between the studies because the studies with the same authors differed in terms of the sample studied, the collection parameters, the study design, and the demographic characteristics. The study by Gerhardt et al ( 2021 ) investigated both GNGT and SST paradigm in the same sample. We have treated these data as a single experiment because splitting the experiments into two different ones would suggest statistical independence, which we argue is not given by using the same sample.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in this study we suspected errors in 2 peak coordinates that were outside the mask when first checked or incongruent with the brain location declared. The first coordinate ( x = − 38, y = 72, z = 44) should indicate a peak in the inferior parietal lobule, whereas this is located far outside the mask (Gerhardt et al 2021 ). The sign of the y -coordinate seems to be incorrect, so that we assume, in line with the reported brain area, that the coordinate should have been x = 38, y = − 72, z = 44.…”
Section: Resultsmentioning
confidence: 99%
“…In ADHD, new and interesting situations with low distraction – as in (laboratory) research – often lead to a temporary decrease in symptoms including hyperactivity ( 37 ). Functional imaging studies on AUD and ADHD showed similar impulsivity and resting state brain networks ( 38 ), but brain activation during inhibition tasks depended on ADHD and AUD severity ( 39 ). These findings, together with our results, suggest that in ADHD a less effective brain network compensates impulsivity, which might be more vulnerable to distractors or a general increased level of stress in real life ( 40 ), but not in a controlled laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is one study comparing ADHD and SUD directly on objective measures of inhibitory control. Gerhardt et al (78) observed more commission errors in ADHD subjects compared with alcohol use disorder subjects in a comprehensive paradigm assessing various cognitive aspects of impulsivity. However, they did not observe any behavioral differences on six other measures.…”
Section: Adhd and Sud Shared Behavioral Deficitsmentioning
confidence: 99%
“…One study directly compared brain activation of ADHD and alcohol use disorder patients as elicited by a comprehensive response inhibition task (78). Authors report more activation of a frontoparietal network, cortical and subcortical motor areas, and occipital areas in alcohol use disorder patients compared with ADHD patients.…”
Section: Cognitive Control-related Areasmentioning
confidence: 99%